Studium působení plazmatu na roztoky chininu - Procházková, Michaela (Vysoké učení technické v Brně. Fakulta chemická, 2020)
Diplomová práce se zabývala roztoky chininu a jejich kvalitou po opracování plazmovými výboji. Tyto výboje se využívají například k odstranění nežádoucích látek z odpadních vod, mezi které můžeme řadit i chinin. Teoretická část je zaměřena na seznámení s problematikou elektrických výbojů v kapalinách a na vlastnosti chininu. V experimentální části byly pomocí UV-VIS spektrofotometrie a fluorescenční spektrometrie sledovány vlastnosti roztoků chininu s obsahem různých elektrolytů. Byly použity dvě odlišné konfigurace plazmových výbojů. Roztoky byly porovnávány na základě rozdílné koncentrace chininu, rozdílných elektrolytů, plazmových výbojů a hodnot pH roztoků. Dále se práce zaměřila na roztoky chininu s elektrolytem dusičnanem sodným. Byla zkoumána časová nestálost roztoků. A také vliv stáří roztoku, způsob opracování a typ zvoleného plazmového výboje na excitační a emisní spektra chininu.

This diploma thesis focuses on quinine solutions and quality of these solutions after applying plasma discharge. These electric discharges can be used to destroy some substances from the water. The theoretical part is focused on description of electric discharges in liquids and on the properties of quinine. In the experimental part, the properties of quinine solutions containing different electrolytes were analysed by UV-VIS spectrophotometer and fluorescence spectroscopy. Two different types of configurations of plasma discharges in liquids were used. Solutions were compared on the base of different concentration of quinine, different electrolytes, different configurations of plasma discharges and pH values of the solutions. Furthermore, the experimental work focuses on quinine solutions with the sodium nitrate. The time instability of the solutions was analysed. Also, the influence of the solution age and different types of the plasma discharge on the excitation and emission spectra of quinine were investigated.
Study of plasma effects on quinine solutions
Keywords: Plazma v kapalinách; chinin; výboj podobný koroně; klouzavý obloukový výboj; UV-VIS spektrofotometrie; fluorescenční spektrometrie.; Plasma in liquids; quinine; corona-like discharge; gliding arc discharge; UV-VIS spectrophotometry; fluorescence spectroscopy.